Risiko Dehumanisasi pada Crowdfunding sebagai Akses Pendanaan Berbasis Teknologi di Indonesia - Gita Widi Bhawika (Jurnal Sosial Humaniora, 2025)
Crowdfunding is the novel phenomenon. This fundraising based technology has increased its popularity since a decade ago. Crowdfunding can help people to funding their initiatives without boundaries because it only need internet connection to ask and give money. It is not necessary to gain relationship between initiator and funder. Yet, from the conventional fundraising point of view, it is important to build relationship to increase the loyal funder who can easily fund the future initiator’s initiatives. Thus, crowdfunding has potential dehumanization risks. This descriptive research will discuss about crowdfunding in Indonesia, and its dehumanization risks. Moreover, this paper will describe crowdfunding phenomenon in Indonesia and also propose the model of crowdfunding’s donor relationship management to minimize the dehumanization risks.